Breed Distribution of the Superoxide Dismutase 1 Gene Polymorphism Associated With Degenerative Myelopathy in a Canine Population From Different Geographical Regions of Turkiye - Yuksel, Merve; Ege, Kerem; Karakus, Ilayda; Akyuz, Bilal (Wiley, 2026)
Background and Objective Canine degenerative myelopathy (CDM) is a progressive neurodegenerative condition that impacts the spinal cord, resulting in paralysis in dogs. CDM is linked to a missense mutation in the superoxide dismutase 1 (SOD1) gene. This study aimed to examine the presence of the SOD1:c.118G>A mutation in the German Shepherd, Golden Retriever, Pomeranian, Toy Poodle and native Kangal Shepherd dog breeds in Turkiye. Methods Blood samples (n = 161) from five breeds, collected from six provinces across five geographic regions of Turkiye, were tested for the prevalence of the mutant allele associated with CDM. All dogs were clinically healthy and sampled for genetic testing. Genotyping was performed using the PCR-RFLP method and gel electrophoresis. Results Genotyping of dogs revealed that 141 had the homozygous wild-type genotype (GG), 20 were heterozygous carriers (AG), and there were no homozygous mutant (AA) individuals. The mutant A allele was determined in Kangal Shepherd, German Shepherd and Toy Poodle dog breeds. The frequency of the mutant allele in the investigated population was identified as 0.062. It was determined that the mutant allele, which was not previously reported in the Kangal Shepherds, was present, and the mutant allele frequency revealed 0.057. Conclusions The SOD1:c.118G>A mutation is present in dog breeds in Turkiye, and is also detected in the Kangal Shepherd, an ancient breed. This finding underscores the importance of genetic testing in dogs, as it is crucial to prevent the spread of mutations in different canine populations. Carrier dogs can be clinically identified to prevent breeding and reduce CDM incidence.
Keywords: degenerative myelopathy; German Shepherd; Kangal Shepherd; restriction fragment length polymorphism-polymerase chain reaction; SOD1 gene; Toy Poodle